Pengukuran Konsentrasi Ozon yang Dihasilkan Dari Penggunaan Raket Nyamuk - Taat Guswantoro (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
The generation of ozone can be done by using high voltage so as to produce electronic discharge which will ionize the oxygen gas particles then recombination of these ions will produce ozone. The mosquito racket exploits a very high potential difference between its nets in order to burn the mosquitoes that trapped between the nets. The use of mosquito rackets in the air greatly enables the occurrence of electronic discharges that will produce ozone. In this study the mosquito racket is inserted in the sheath then activated for 60 minutes and ozone concentration is measured using ozonmeter every 5 minutes, the mosquito racket has an output voltage of 2500 volts and 5000 volts. On a 2500 volts mosquito racket the maximum ozone concentration of 1.70 ppm occurs at 35 minutes with an average rate of ozone production of 0.0133 ppm / min. On a 5000 volt mosquito rack a maximum ozone concentration of 11.40 ppm occurs at 35 minutes with an average rate of ozone production of 0.277 ppm / min. Keywords: Ozon, Electronic discharge, Mosquito racket.